Structural and molecular basis for hyperspecificity of RNA aptamer to human immunoglobulin G - Miyakawa, Shin (Cold Spring Harbor Laboratory Press, 2008)
Potential applications for functional RNAs are rapidly expanding, not only to address functions based on primary nucleotide sequences, but also by RNA aptamer, which can suppress the activity of any target molecule. Aptamers are short DNA or RNA folded molecules that can be selected in vitro on the basis of their high affinity for a target molecule. Here, we demonstrate the ability of RNA aptamers to recognize—and bind to—human IgG with high specificity and affinity. An optimized 23-nucleotide aptamer, Apt8-2, was prepared, and was shown to bind to the Fc domain of human IgG, but not to other IgG's, with high affinity. Apt8-2 was observed to compete with protein A, but not with the Fcγ receptor, for IgG binding. NMR chemical-shift analyses localized the aptamer-binding sites on the Fc subdomain, which partially overlaps the protein A binding site but not the Fcγ receptor binding site. The tertiary structures of the predicted recognition sites on the Fc domain differ significantly between human IgG and other species of IgGs; this, in part, accounts for the high specificity of the selected aptamer. Apt8-2 can therefore be used as a protein A alternative for affinity purification of human IgG and therapeutic antibodies. Using Apt8-2 would have several potential advantages, raising the possibility of developing new applications based on aptamer design.